Parenting Styles and Child’s Well-Being: The Mediating Role of the Perceived Parental Stress - Delvecchio, Elisa (Eur J Psychol, 2020)
In the last decades, consensus from laymen, scholars, and policy-makers has emphasized the role of child-parent relationships to promote child’s development and positive well-being. Parenting style was claimed as one of the crucial factors for the child’s positive adjustment. The main aim of the present study was to investigate the relationships between authoritative and authoritarian parenting styles and child’s difficulties. The mediational role of parent’s perception of a difficult child on the above mentioned relation was taken into account. The study was carried out on a sample of 459 couples including mothers (n = 459) and fathers (n = 459) of children aged 2 to 10 years old who filled in the Parenting Styles & Dimensions Questionnaire short version, the Strengths and Difficulties Questionnaire, and the Parenting Stress Index-short form. Main findings indicated that authoritative style was associated with less child’s maladjustment, while the authoritarian one showed the opposite association. These relationships were partially mediated by the perception of a difficult child, which partially explained the link between parenting style and child’s problems. Above and beyond the role of parent’s perception as a difficult child, parenting styles had an important effect on child’s difficulties. Future studies should replicate these results with other samples, use the spouse version of the parenting styles, control the effect of socio-economic status and other variables related to family functioning, as well as to consider the child’s perception regarding parents’ parenting style.